Complete genome assembly and methylome dissection of Methanococcus aeolicus PL15/Hp - Fomenkov, Alexey; Weigele, Peter; McClung, Colleen; Madinger, Casey; Roberts, Richard J. (Frontiers in Microbiology, 2023)
Although restriction-modification systems are found in both Eubacterial and Archaeal kingdoms, comparatively less is known about patterns of DNA methylation and genome defense systems in archaea. Here we report the complete closed genome sequence and methylome analysis of Methanococcus aeolicus PL15/Hp, a strain of the CO2-reducing methanogenic archaeon and a commercial source for MaeI, MaeII and MaeIII restriction endonucleases. The M. aeolicus PL15/Hp genome consists of a 1.68 megabase circular chromosome predicted to contain 1,615 protein coding genes and 38 tRNAs. A combination of methylome sequencing, homology-based genome annotation, and recombinant gene expression identified five restriction-modification systems encoded by this organism, including the methyltransferase and site-specific endonuclease of MaeIII. The MaeIII restriction endonuclease was recombinantly expressed, purified and shown to have site-specific DNA cleavage activity in vitro.